Meningkatkan Hasil Belajar Siswa Pada Pelajaran PAK “Aku Bertumbuh Dan Berkembang Dalam Kebaikan” Menggunakan Metode Problem Based Learning Dengan Media Gambar Dan Video Di Kelas III SD N 155675 Tapian Nauli 3C TAP-TENG - Ira Astrida Br. Sembiring (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Catholic Religious Education is a field of study that provides teaching about how to behave and act and have adequate knowledge and skills for students, especially Class III students at SD N 155675 Tapian Nauli 3C in living their lives according to the teachings of Jesus Christ. In the context of the Independent Curriculum which emphasizes the Pancasila student profile, researchers emphasize the dimension of independence which is based on the importance of forming strong character and mental attitudes in each student, especially in facing complex global challenges. One learning model that can be applied is Problem Based Learning (PBL) or problem-based learning. The objectives of the research include (1) to determine whether video and image media using the PBL model in class III of SD N 155675 Tapian Nauli 3C Tap-Teng can increase students' learning motivation, (2) to determine the increase in student learning outcomes in PAK lessons in class III SD N 155675 Tapian Nauli 3C Tap-Teng using image and video media. The type of research used is qualitative with a descriptive approach. The analysis and data collection techniques used are by examining data available from various sources, namely; questionnaires, interviews, observations and observation sheets that have been recorded, reported and documented, including tests, portfolios and score lists and have three components, namely: a. Data presentation. b. Data reduction c. Drawing conclusions. From the problems found, the author concludes that through image and video media, student learning outcomes can be improved every time a formative test is held. This research uses two cycles of classroom action research. The target of this research is class III students at SD N 155675 Tapian Nauli 3C. Data was obtained from the results of formative tests, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning outcomes had increased from pre-cycle to cycle II after using Image and Video Media. The research implementation process showed good changes in student learning outcomes. The level of achievement of student learning outcomes in pre-cycle class III was (33.33%), after conducting research in cycle I, completeness of class III learning (50%), and in cycle II, completeness of class III learning (91.67%). So, the conclusion of this research is that using Image and Video Media can improve the learning outcomes of class III students at SD N 155675 Tapian Nauli 3C, and using Image and Video Media is an alternative that can be used to achieve more satisfactory student learning outcomes. .